Significant advantages for first line treatment with TNF-alpha inhibitors in pediatric patients with inflammatory bowel disease – Data from the multicenter CEDATA-GPGE registry study - Claßen, Merle; de Laffolie, Jan; Claßen, Martin; Schnell, Alexander; Sohrabi, Keywan; Hoerning, André (Frontiers in Pediatrics, 2022)
Background and aims In recent years, biological agents, such as anti-TNF-α blockers, have been introduced and have shown efficacy in pediatric patients with inflammatory bowel disease (IBD). Here, the prescription mode differentiated into a first/second line application, and efficacy and side effects are evaluated beginning from 2004 until today. Methods Statistical analyses of the prospective and ongoing CEDATA multicenter registry data from the Society of Pediatric Gastroenterology and Nutrition (GPGE) were performed for patients receiving a biological agent at least once during the period from June 2004 until November 2020 (n = 487). The analyzed parameters were patient demographics, disease extent and behavior, prior or concurrent therapies, duration and outcome of biological therapy, disease-associated complications, drug-related complications, laboratory parameters and treatment response as determined by the Physician’s Global Assessment. Results Crohn’s disease (CD) was present in 71.5% of patients, and 52% were boys. Patients showed high disease activity when receiving a first-line TNF-α blocker. After 2016, patients who failed to respond to anti-TNF-α induction therapy were treated with off-label biologics (vedolizumab 4.3% and ustekinumab 2.1%). Propensity score matching indicated that patients with CD and higher disease activity benefitted significantly more from early anti-TNF-α therapy. This assessment was based on a clinical evaluation and lab parameters related to inflammation compared to delayed second-line treatment. Additionally, first-line treatment resulted in less treatment failure and fewer extraintestinal manifestations during TNF-α blockade. Conclusion First-line treatment with anti-TNF-α drugs is effective and safe. An earlier start significantly reduces the risk of treatment failure and is associated with fewer extraintestinal manifestations during longitudinal follow-up.